2017
DOI: 10.3892/or.2017.6094
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xanthohumol on Th1/Th2 balance in a breast cancer mouse model

Abstract: Xanthohumol (XN), a prenylflavonoid found in the hop plant, Humulus lupulus, exhibits a variety of biological activities. Numerous studies have reported that XN inhibits the growth of many types of cancer cells, but the effects of XN on tumor immunity have not yet been studied. We explored the effect of XN on Th1/Th2 balance and the underlying mechanism based on a BALB/c-4T1 breast cancer mouse model. The results showed that XN significantly slowed down tumor growth and inhibited expression of antitumor prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…They observed no changes in mouse body weight. Furthermore, administration of XN in xenograft models of breast, leukemia, prostate, pancreatic, gastric, and cholangiocarcinoma cells inhibits tumor growth [29,41,57,58,59,60,61,62,63]. Taken together, these data suggest that XN and its derivatives show promise in future studies.…”
Section: Discussionmentioning
confidence: 81%
“…They observed no changes in mouse body weight. Furthermore, administration of XN in xenograft models of breast, leukemia, prostate, pancreatic, gastric, and cholangiocarcinoma cells inhibits tumor growth [29,41,57,58,59,60,61,62,63]. Taken together, these data suggest that XN and its derivatives show promise in future studies.…”
Section: Discussionmentioning
confidence: 81%
“…Mast cells have the ability to facilitate tumor proliferation and invasion directly,and indirectly promote tumor proliferation and invasion by regulating tumor microenvironment [22], it may provide further evidence for Mast cells can be applied in the adjuvant treatment of mammary adenocarcinoma and melanoma [23]. Previous studies have shown that Th2 cells, T helper cells, and Mast cells may play key roles in the development and invasion of cancer [24][25][26][27], our studies show that these immune cells may play a role in gastric cancer.…”
Section: Discussionmentioning
confidence: 95%
“…CDDO-Im (a synthetic triterpenoid: 1[2-Cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl]imidazole) has an extensive documentation as an immunomodulation agent ( 253 255 ), and xanthohumol (XN) (a prenylated chalcone flavonoid) is an antileukemia agent ( 256 259 ) and is a polarizing agent in murine models of breast cancer ( 260 ). Phytocompounds and their synthetic derivatives are able to polarize macrophages inducing anti-tumorigenic phenotype/functions ( 253 , 260 262 ). For example, we show that NSCLC patient TANKs treated with metformin, CDDO-Im, and XN decreases VEGF production (Figure 5 ) and increases perforin content.…”
Section: Pharmacological and Immunotherapeutic Combination Targeting mentioning
confidence: 99%